Modeling the structure of the sensitive element of the magnetoresistic converter - Zinkovsky, Yu. F.; Vityaganets, A. I. (Technology and design in electronic equipment, 2017)
In the analysis of the electromagnetic structure the distribution and direction of current and the tangential electric field (E-fields) are found. The sensing element of the converter, which is used in the magnetoresistive system, is designed to measure active power in the frequency range from DC to hundreds of megahertz. An expression for the input resistance of the measuring transducer of the active power required for calculating the current in the film is obtained.The simulation of the current distribution and tension of the tangential electric field in the three-dimensional structure of the sensitive element of the magnetoresistive measuring converter of active power was carried out. Knowing the direction of current along the structure it is possible to dampen the parasitic components of the current across the structure, which allows improving the topology of the sensitive element of the converter.